Brain Microhemorrhages Detected on T2*-Weighted Gradient-Echo MR Images - Tsushima, Yoshito; Aoki, Jun; Endo, Keigo (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Multifocal microhemorrhages have been reported to be commonly found in the brain of patients with systemic hypertension and spontaneous brain hemorrhage. The factors associated with these lesions detected on T2*-weighted gradient-echo images were examined to determine whether these lesions serve to indicate different types of microangiopathy and to predict a patient’s risk for symptomatic hemorrhage.METHODS: The study population consisted of 2164 patients who underwent 2416 consecutive brain MR imaging studies performed during 3 years. The patients with intracerebral hemorrhages due to vascular malformations, neoplasms, trauma, or intracranial surgery and those with incomplete medical records were excluded; 2019 cases were analyzed.RESULTS: The overall incidence of microhemorrhages was 9.8%, predominantly in the lentiform nucleus (n = 96), thalamus (n = 88), and cortical-subcortical region (n = 93). Presence of microhemorrhages had the highest significant correlation with history of hemorrhagic stroke (P < .0001); advancing age, hypertension, and prominent white matter hyperintensity on T2-weighted images had the next highest significant correlation. Cortical-subcortical microhemorrhages were more frequently observed in patients who had previous lobar hemorrhagic stroke (P < .005). Among 139 patients with microhemorrhages who could be clinically followed up for more than 1 month, four (2.9%) had new hemorrhagic stroke.CONCLUSION: The presence of microhemorrhages may be not only a direct marker of bleeding-prone small-vessel diseases but also an indicator of different types of microangiopathy and a predictor of further hemorrhagic stroke.